2015
DOI: 10.1088/0031-9155/60/5/1945
|View full text |Cite
|
Sign up to set email alerts
|

Differences in 3D dose distributions due to calculation method of voxel S-values and the influence of image blurring in SPECT

Abstract: This study compares 3D dose distributions obtained with voxel S values (VSVs) for soft tissue, calculated by several methods at their current state-of-the-art, varying the degree of image blurring. The methods were: 1) convolution of Dose Point Kernel (DPK) for water, using a scaling factor method; 2) an analytical model (AM), tting the deposited energy as a function of the source-target distance; 3) a rescaling method (RSM) based on a set of high-resolution VSVs for each isotope; 4) local energy deposition (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 55 publications
3
39
0
1
Order By: Relevance
“…A recent paper by Pasciak et al [37] demonstrated in 90 Y PET that as long as the full-width at half-maximum point spread function (FWHM PSF ) is wider than the dose point kernel FHWM dose kernel , the LDM is in closer agreement with the Fig. 5d in [38]). In other words, the energy transport among neighbouring voxels is simulated by the blurring effect of the PSF, which actually constitutes a first convolution, intrinsic in the imaging process itself.…”
Section: Local Deposition Methodssupporting
confidence: 54%
“…A recent paper by Pasciak et al [37] demonstrated in 90 Y PET that as long as the full-width at half-maximum point spread function (FWHM PSF ) is wider than the dose point kernel FHWM dose kernel , the LDM is in closer agreement with the Fig. 5d in [38]). In other words, the energy transport among neighbouring voxels is simulated by the blurring effect of the PSF, which actually constitutes a first convolution, intrinsic in the imaging process itself.…”
Section: Local Deposition Methodssupporting
confidence: 54%
“…9,[17][18][19][20][21][22][23] Image-based 3D dosimetry can be performed in several ways: direct Monte Carlo (MC) simulation, which is considered the gold standard; 9,[24][25][26][27][28][29][30] convolution calculations by voxel S-values, reliable in nearly uniform density tissue; 19,[31][32][33][34][35][36] local energy deposition method. 18,20,[36][37][38][39] Activity distribution quantification by SPECT is the major concern, due to physical and clinical degrading factors of the images. Physical factors [i.e., attenuation, scatter, partial volume effects (PVEs), noise] require well known corrections for attenuation and scatter, whereas presently, corrections for PVE (on a voxel-by-voxel basis) are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The relative calibration plays an important role, imposing the area under an activity-volume-histogram to be the total activity theoretically present in the volume-of-interest (VOI). Considering that with spatial resolution of 10-13 mm, the local energy deposition is almost equivalent to convolution dosimetry, 36 the absorbed dose to voxel can be considered linearly related to the voxel activity. So, with respect to an absolute calibration, the relative calibration causes a shift of the obtained cDVHs toward higher absorbed doses, making T III.…”
mentioning
confidence: 99%
“…The 90 Y dose calculation used the local deposition method (LDM),20, 21 which was previously demonstrated to be the most accurate when using SPECT imaging 22. In this technique, 90 Y β‐particles released by decay within a voxel deposit all energy locally with the same voxel.…”
Section: Methodsmentioning
confidence: 99%